Performance of Different "Lab-On-Chip" Geometries for Making Double Emulsions to Form Polystyrene Shells. (17th February 2018) - Viza, N. D.; Harding, D. R.
Abstract: Fluid properties and the geometry of lab-on-chip (LOC) designs together affect the formation of double emulsions for making inertial confinement fusion targets. Critical fluid properties include the fluids' velocities and interfacial tension—a coupled effect that is best characterized by the capillary number (Ca)—and the relative volumetric flow rates (φ). The important geometry of the LOC is the orientation of the channels where they intersect (junction) and the spacing between successive junctions. T-junctions and focus-flow devices were tested. The latter geometry of a double cross (focus flow) performed better: single-emulsion droplets were formed over a wide range of fluid parameters (0.03 < φ < 0.17 and 0.0003 < Ca < 0.001) at the first junction, and double emulsions were formed over a more limited range (φ > 0.5 and Ca < 0.4) at the second junction. A LOC design using the focus-flow design formed water–oil–water double emulsions with the oil phase containing polystyrene. The double emulsions yielded shells with an outer dimension ranging from 2.3 ± 0.07 to 4.3 ± 0.23 mm and a wall thickness ranging from 150 μm to 1.6 mm. The value of the flow-rate ratio at the second junction provided the most effective parameter for controlling the inner diameter, outer diameter, and wall thickness of the shell.